A Few Remarks on Succumbing to Temptation - Dobrosz-Michiewicz, Karolina (Following Rhetoric, Stylistics and Journalism. A Volume Dedicated to Professor Barbara Bogołębska, 2019)
The phenomenon of succumbing to temptation has received many studies in the field of ethnography, sociology or in general – the research on morality. However, its results are different in the case of musings based in social psychology. My review of literature in abovementioned, pointed me to the existence of two dominant research perspectives in the studies on the subject: the perspective of proper resocialization psychology (describing the phenomenon in terms of antisocial behavior) and psychology of morality. The results of studies show that in most cases, people tend to be tempted to take advantages in order to gain some advantages, despite the declared recognition of legal and ethical norms prohibiting the appropriation of other people’s property. This note becomes the starting point for the author of this article. What else, if not legal legalism, can be a buffer to deter a man from temptation? The paper presents the research on the relationship between personality and succumbing to temptation.